Comparison of ELISA and PCR of the 18S rRNA gene for detection of human strongyloidiasis using serum sample. Issue 5 (4th May 2019) - Javanian, Mostafa; Gorgani-Firouzjaee, Tahmineh; Kalantrai, Narges
Abstract: Background: Strongyloides stercoralis infection is a neglected tropical disease with global distribution which is fatal in immunosuppressed patients. This study aimed to determine the prevalence of strongyloidiasis in immunocompromised individuals and cases with infectious diseases, as well as comparing ELISA and conventional PCR with coprological examination, in the central parts of Mazandaran province, northern Iran. Methods: A single serum anda fresh stool samples were obtained from 272 and 220 patients, respectively. Serum was tested by ELISA and PCR of the 18S rRNA gene, and stool samples were examined with various parasitological methods. The optimum point for ELISA reaction and cut-off points were recognized by receiver operating characteristic curves (ROC). Results: Out of 220 stool specimens, 14(6.3%) cases were positive for S. stercoralis larvae. The overall seroprevalence rate was 27.9% (76/272). The seroprevalence rate was 25.2% and 30.1% in immunocompromised group and patients with infection, respectively. Based on the ROC curve of ELISA compared with microscopy, the optimum cut-off point was 12.74 with 79% sensitivity and 76% specificity. The optimum cut-off point was 10.42 with 69% sensitivity and specificity using ROC curve of ELISA compared with PCR. Conclusions: This study seroprevalence rate for Strongyloides infection in the studied group. It also observed that the ELISA technique and the PCR used here have 100 demonstrated a high % sensitivity and acceptable specificity compared with coprological examination. It seems that the ELISA technique is a good screening assay in ruling out strongyloidiasis in such patients.